Mapping of Waste Management Planning Based on Society and Geographic Conditions - Niluh Widyaningsih; Shunsuke Sasaki (Geoplanning: Journal of Geomatics and Planning, 2020)
Household solid waste is the major environmental issue, not only in big cities but also in the suburban areas. Setia Asih Village location is in Kecamatan Tarumajaya, Kabupaten Bekasi. Bekasi is closed with Jakarta and it has unique characteristics, such as dual market economy; administration system; and social culture of the local people. Setia Asih Village has tremendous unmanaged household solid waste. It covers the land and river. This research paper used qualitative approach due to the limited of statistical data on the village level in Indonesia. The preliminary observation showed that local people do not have any knowledge or information about managing their household solid waste. Their local government does not have any responsibility to manage the household solid waste on the village level. It becomes local people responsibility. There is lack coordination among stakeholders in household solid waste management at Setia Asih Village. I conducted the solid waste management training to 300 people and Focus Group Discussion (FGD) with each Dusun (lower level than village) representatives. I found that local people have solutions to solve their household solid waste problem. Local government builds a new waste bank as Corporate Social Responsibility (CSR) from one of the state-owned enterprise.